The verses of Kashagan Kurjimanuly are devoted Sufi of Eskali - Ahmetbekova, A. K. (Journal of Oriental Studies, 2016)
The article considers poetry of Kazakh poet of XIX-XX centuries Kurzhimanuly Kashagan. This poetry was improvised in responseto the inhospitality of Eskali sufi who justifi ed his actions by religiousness, as the instrument of poets – dombra – is a stick of the devil.Through analysis of religious works of Kashagan, the author distinguishes collision of two interpretations of Islam in Kazakhsociety.